Widows in the Hispano-Roman - Suevic/ Visigothic Councils of Hispania - Ferreiro, Alberto (Vox Patrum, 2022)
The Church Fathers did not neglect to give attention to widows and articulate what they believed was their role in the Church. Modern studies are quite abundant focusing mainly from the New Testament, the early Church, and the Middle Ages. One era that has been marginalized is widows in sources from late antique Roman and Suevic-Visigothic Hispania. Early Christian writers are noted for background only, the focus here are the conciliar texts dating from the fourth through seventh centuries.